Analysis and Design of AI and AR-Based Applications with a UIUX Approach to support Inclusive Learning for students with Disabilities - Swalaganata, Galandaru; Andarwati, Mardiana; Al-Islama Achyunda Putra, Firnanda; Assih, Prihat; Sudarwati, Ririn; Bramasta, Yara (Universitas Dr. Soetomo, 2025)
The integration of Artificial Intelligence (AI) and Augmented Reality (AR) in education holds transformative potential, particularly in fostering inclusive learning environments for students with disabilities. This study investigates the integration of Artificial Intelligence and Augmented Reality to advance inclusive education. This research examines the analysis and design of AI and AR-based applications, employing a User Interface and User Experience (UI/UX) approach to cater to the diverse needs of students with physical, sensory, or cognitive impairments. By emphasizing inclusive design principles, the study aims to develop adaptive and accessible educational tools that promote engagement, deepen understanding, and improve learning outcomes. The research adopts a multidisciplinary methodology, combining insights from accessibility standards, UI/UX design frameworks, and educational technologies. Key objectives include identifying accessibility barriers, designing user-centric interfaces, and evaluating the effectiveness of AI-driven personalization and AR-enhanced interactivity in real-world learning scenarios. Preliminary findings highlight the importance of responsive and adaptive interfaces in facilitating equitable access and promoting active participation among students with disabilities. The study underscores the role of innovative technologies in bridging gaps in traditional education systems, ultimately promoting an inclusive and empowering learning experience. This research contributes to the broader discourse on leveraging technology to ensure educational equity and inclusion in the digital age.